Template directed synthesis of porous tin (IV) oxide - Zhu, Jie (2009)
In the past fifteen years, porous inorganic materials templated by organic molecules have exhibited superior properties over their conventional counterparts from simple sol-gel technique. However , synthesis of porous metal oxides usually suffers from two challenges: high reaction rates of oxide precursors and low thermal stability of porous structure. As a result, ill-defined porous structures are formed and the subsequent calcinations can lead to destruction of porous skeletons. Therefore, developments of techniques that can overcome these problems are in high demand.